Radical Knowledge Management: Using Lessons Learned From Artists to Create Sustainable Workplaces - Barnes, Stephanie (Frontiers in Artificial Intelligence, 2021)
This study weaves together research that has been published over the last 20 years and creates a narrative about how we can change our organisations so that they are fit-for-purpose in the 21st century. Using knowledge management as the starting point, the question “How do we move forward in a sustainable, holistic way to create organisations that are healthy and balanced among social, environmental, and financial performance (triple bottom line)?” needs to be answered. This brand new form of knowledge management is called radical knowledge management (radical KM).